Predictors of Language Service Availability in U.S. Hospitals - Melody K. Schiaffino; Mona Al-Amin; Jessica R. Schumacher (International Journal of Health Policy and Management, 2014)
Background Hispanics comprise 17% of the total U.S. population, surpassing African-Americans as the largest minority group. Linguistically, almost 60 million people speak a language other than English. This language diversity can create barriers and additional burden and risk when seeking health services. Patients with Limited English Proficiency (LEP) for example, have been shown to experience a disproportionate risk of poor health outcomes, making the provision of Language Services (LS) in healthcare facilities critical. Research on the determinants of LS adoption has focused more on overall cultural competence and internal managerial decision-making than on measuring LS adoption as a process outcome influenced by contextual or external factors. The current investigation examines the relationship between state policy, service area factors, and hospital characteristics on hospital LS adoption.